Ayo berdoa sebelum tidur=Lets pray before we sleep Rafatul athfah ; ilustrator, Adriana A. Amir ; editor, Kiki Sulistiyani, Setya Bhawono, M. H. Eddy - ATHFAH, Rafatul; Amir, Adriana A; Sulistiyani, Kiki; Bhawono, Setyo; Eddy M. H. (Erlangga, 2006)
40 hlm. : ilus. ; 22x28 cm.